(untitled) (Swiss Medical Weekly, 2017)
BACKGROUND Securing the adherence over time to contraception by adolescent girls is a challenge. Until now little was known about this topic in Switzerland. The aim of our study was to determine contraceptive continuation rates among adolescents in this country and assess possible predictive factors for discontinuation. METHODS A prospective observational cohort study of 12- to 19-year-old girls starting contraception was performed. Patients were interviewed again after 1 year by phone, email or postal mail. RESULTS A total of 204 patients were included, of whom 85.8% chose a combined oestrogen-progestogen pill. The answer rate 1 year later was 71%. Among these, continuation of the initially prescribed contraceptive method was observed in 73.1%. Factors statistically affecting the continuation rate were the initial contraceptive method, the place of residence and sexual activity after 1 year. Classification of contraceptive methods in decreasing order of continuation rate was the following: long acting reversible contraception (LARC) methods, oestrogen-progestogen pills, injections, progestogen pills, patches and rings. Major reasons reported for stopping the prescribed contraceptive method were ending sexual relations (54.3%), developing side effects (34.3%) or changing to another contraceptive method (22.9%). Neither age, nationality, smoking, occupation, nor the legal representative’s knowledge of the contraception influenced adherence. CONCLUSION Contraceptive continuation rate was high among the adolescent population studied. The only predictive factor of discontinuation was the contraceptive method. Our study also reveals that respecting teenagers’ confidentiality is essential as it does not negatively impact the continuation rate. The significant impact of the type of contraception on continuation rates stresses the importance of individualised counselling.